Amanah-Based Household Accounting: A Muslim Family Perspective - Ramadhani, Febrina Nur; Ekaviana, Dessy; Mujahidi, Khairul (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2025)
This study aims to explore the meaning of trust-based household accounting from the perspective of Muslim families. Employing a qualitative approach and transcendental phenomenology method, data were collected through in-depth interviews with five Muslim families from diverse socio-economic backgrounds. The findings reveal that trust-based household accounting is understood as a process of managing family finances grounded in Islamic spiritual values, responsibility, justice, transparency, and deliberation as part of fulfilling one’s duty as a servant of Allah and leader within the family. This research highlights the importance of integrating ethical and religious values into domestic accounting practices and offers a conceptual contribution to the development of value-based accounting.